Desentralisasi dan Kepemimpinan Pendidikan Dalam Meningkatkan Mutu Lembaga Pendidikan - Rahmad Rafid; Supriadi Supriadi; Moh. Hilman Fikri; A.Taufiq Hidayat; Riski Febria Nurita (Journal on Education, 2024)
This research focuses on the problem of how the form of Education Management in the frame of decentralization and educational leadership in improving the quality of educational institutions. This study uses qualitative methods that are literature studies, using descriptive analysis, with data collection techniques through books, journals and research-related. The results showed that the globalization process requires the millennial generation of the nation to respond to the development of Education. The enactment of the decentralization policy has an impact on the management of education in Indonesia, especially in areas that have received authority in the management of education, and the enactment of educational autonomy gives flexibility to heads of educational institutions to manage the institutions they lead into a quality institution (quality) which includes school program planning and Evaluation Management, curriculum management, teaching and learning process management, facilities/infrastructure management, financial management, student Service Management, School relationship management with the community, as well as school climate Management in accordance with the mandate in the National Education System Law. Improving the quality of educational institutions required educational leadership that has an orientation on quality. Principal leadership will be effective if supported by strong organizational culture conditions. Leadership can provide orientation to the formation of a strong organizational culture (Strong Cultural) it aims to achieve the goals of the school, namely improving the quality of education in educational institutions